2007
DOI: 10.1016/s0828-282x(07)71014-0
|View full text |Cite
|
Sign up to set email alerts
|

The Brugada syndrome in Canada: A unique French-Canadian experience

Abstract: B rugada syndrome (BS) involves a cardiac sodium channel abnormality and is associated with a high risk of ventricular arrhythmias and sudden cardiac death in individuals with a structurally normal heart. BS is mainly recognized in the specialized electrophysiology community. Characteristic electrocardiograms (ECGs) show a typical pattern of a right bundle branch block-like complex and ST segment elevation in leads V1 to V3 (1,2). In a recent consensus statement (3), three types of repolarization patterns were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Interestingly, the recent ESC guidelines give a class IIa indication (level of evidence C) for an ICM (instead of an ICD) in Brugada patients with recurrent unexplained syncope who are at low risk of SCD [12]. Currently, there is limited published data on the use of ICM in patients with Brugada syndrome [5,10,11,[16][17][18]. A few case reports in Brugada patients with presumed nonarrhythmogenic syncope have demonstrated the detection of self-terminating sustained ventricular arrhythmia by the ICM [16,17].…”
Section: Role Of Icm In Brugada Syndromementioning
confidence: 99%
“…Interestingly, the recent ESC guidelines give a class IIa indication (level of evidence C) for an ICM (instead of an ICD) in Brugada patients with recurrent unexplained syncope who are at low risk of SCD [12]. Currently, there is limited published data on the use of ICM in patients with Brugada syndrome [5,10,11,[16][17][18]. A few case reports in Brugada patients with presumed nonarrhythmogenic syncope have demonstrated the detection of self-terminating sustained ventricular arrhythmia by the ICM [16,17].…”
Section: Role Of Icm In Brugada Syndromementioning
confidence: 99%
“…43 Similar results of low annual incidence of arrhythmic events in asymptomatic patients have been published in several studies so far. [44][45][46][47][48][49][50][51][52][53][54] From the most recent studies, it is evident that the annual incidence of arrhythmic events in asymptomatic individuals with Brugada ECG pattern is about 1%. Arrhythmic events will occur as VF without any warning symptoms in about 50% of cases.…”
Section: Prognosis Of Asymptomatic Individuals With Brugada Ecg Phenomentioning
confidence: 99%
“…The eight included studies comprised 1364 patients, of which participant-level data were provided for all. Since additional patients were enrolled and follow-up extended beyond the publication date in some studies, 2022 the number of patients in the original publications may differ from those reported here. Follow-up methods in these studies were identical to those reported in the original publications.…”
Section: Methodsmentioning
confidence: 87%